Breastfeeding Self-Efficacy and Level of Acculturation among Low-Income Pregnant Latinas (International Journal of Child Health and Nutrition, 2018)
Objective: The objective of the study was to determine whether less acculturated, compared to more acculturated, low-income pregnant Latinas, report higher levels of breastfeeding self-efficacy. Data on level of acculturation and breastfeeding self-efficacy were collected from 253 pregnant low-income Latinas.Methods: This study was cross-sectional.Results: This study found that less acculturated, compared to more acculturated, low-income pregnant Latinas had significantly higher breastfeeding self-efficacy.Conclusions: Evidence suggests that breastfeeding self-efficacy is one of the strongest modifiable factors linked to high breastfeeding rates. Moreover, prenatal interventions designed to increase breastfeeding self-efficacy have effectively done so. Taken together it appears that one strategy practitioners and researcher may consider to increase breastfeeding rates among more acculturated low-income Latinas is to design a culturally appropriate prenatal breastfeeding intervention aimed at improving breastfeeding self-efficacy.